Impactos da manufatura aditiva no modelo de negócio - Franco, Denise (Universidade Federal de São Carlos, 2019)
A change in consumption has impacted the industrial production, which currently tends to a low volume of production of customized products. Stay competitive in the face of these Fourth Industrial Revolution trends, companies have been looking for new manufacturing techniques to equip themselves with the tools needed for greater flexibility and economic output. Additive Manufacturing can be considered as such technique and has become one of the major disruption phenomena that will impact companies. The greatest breakthrough potential of this technology lies clearly in industrial applications and how they will influence the business model. Therefore, this research aimed to explore the impacts of AM in the business model Canvas. Motivations and limitations for the AM implementation were also investigated. For this, a systematic literature review together with a specialist’s panel, a multiple case study and professionals’ interviews were carried out with the purpose of refining and testing the theory. Thus, the research sought a balance between the explanation of literature and practice. With the results of the research the AM impacts on business model, and its motivations and limitations were identified. Finally, research propositions were suggested. It has been empirically proven that the AM adoption leads to increased democratization of production, intensified information flow, increased environmental impact, and negative impact on workers' health and safety. In addition, the novelty for the literature is that the AM makes the production process more complex and leads to the company's culture change. The limitations for the AM adoption unpublished for the literature were wrong image of the technology and lack of willingness to test.
Impacts of additive manufacturing on business model
Keywords: Impressão 3D; Efeitos; Modelo de negócio CANVAS; Motivações; Limitações; 3D printing; Effects; Business model CANVAS; Motivations; Limitations; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO